Hybridations du récit dans les œuvres d’Éric Reinhardt (TEST Ticontre. Theory Text Translation, 2016)
Les romans d'Eric Reinhardt intègrent des types de discours très hétérogènes: mathématiques, économie, médias, poésie s'y invitent. L'écrivain est aussi intéressé par le croisement des différentes disciplines artistiques: danse, architecture, musiques, peinture...  Pour Eric Reinhardt, l'hybridation est un moyen de renouveler les codes du romans, en inventant de nouvelles formes, mais c'est aussi un réalisme nouveau, parce que notre société accumule les langages disparates. Le nombre croissant d'inclusions dans ses six romans révèle les facettes multiples de l'homme contemporain, qui a perdu son unité. Eric Reinhardt’s novels mix up heterogeneous typologies of discourse, embodying in the narrative dimension different sectorial languages, such as mathematics, economy, media, poetry. His literary experience is also deeply concerned with the intersection of different artistic disciplines: dance, architecture, music, visual art. The paper aims at demonstrating how in E. Reinhardt’s works hybridization is a way to renew the tradition of the novel, its codes and languages, creating new forms. Hybridization, however, also represents an effort toward a new realism, insofar as it allows the reproduction of the disparate languages simultaneously crossing the current communication environment. The increasing number of inclusions of various materials in the six novels of E. Reinhardt reveals the multiple aspects of the contemporary mind after the loss of its entirety.